Pelatihan Penyusunan Bahan Ajar Digital Bilingual Berbasis Islamic Values dengan Book Creator - Pujiati, Tri; Fajar, Fajar; Dzikrulloh, Dzikrulloh (Keris: Journal of Community Engagement, 2024)
Nurul Amanah Pesantren is one of the boarding schools located in Bangkalan, Madura. The problem facing the partners is that there is no digital bilingual teaching materials based on Islamic values developed by the teaching staff at the boarding school. The purpose of this community service activity is to educate teachers at Nurul Amanah Pesantren in creating digital bilingual teaching materials using the Book Creator application. This community service activity is packaged in 3 stages (1) identification and development of partner groups; (2) implementation of training program for creating digital bilingual teaching materials based on Islamic values; and (3) evaluation of activities. The training is also packaged in the form of teaching materials in two languages, namely Indonesian and English so that the learners' English proficiency becomes better. Not only that, this training is designed to provide training to teachers to create teaching materials with an Islamic character in order to form an Islamic character in the students. The results of this activity provide positive benefits for teachers to compose digital teaching materials using bilinguals.